Impact of age at onset and newborn screening on outcome in organic acidurias. Issue 3 (21st December 2015) - Heringer, Jana; Valayannopoulos, Vassili; Lund, Allan M.; Wijburg, Frits A.; Freisinger, Peter; Barić, Ivo; Baumgartner, Matthias R.; Burgard, Peter; Burlina, Alberto B.; Chapman, Kimberly A.; i Saladelafont, Elisenda Cortès; Karall, Daniela; et al.
Abstract: Background and aim: To describe current diagnostic and therapeutic strategies in organic acidurias (OADs) and to evaluate their impact on the disease course allowing harmonisation. Methods: Datasets of 567 OAD patients from the E‐IMD registry were analysed. The sample includes patients with methylmalonic (MMA, n  = 164), propionic (PA, n  = 144) and isovaleric aciduria (IVA, n  = 83), and glutaric aciduria type 1 (GA1, n  = 176). Statistical analysis included description and recursive partitioning of diagnostic and therapeutic strategies, and odds ratios (OR) for health outcome parameters. For some analyses, symptomatic patients were divided into those presenting with first symptoms during (i.e. early onset, EO) or after the newborn period (i.e. late onset, LO). Results: Patients identified by newborn screening (NBS) had a significantly lower median age of diagnosis (8 days) compared to the LO group (363 days, p  < 0.001], but not compared to the EO group. Of all OAD patients 71 % remained asymptomatic until day 8. Patients with cobalamin‐nonresponsive MMA (MMA‐Cbl − ) and GA1 identified by NBS were less likely to have movement disorders than those diagnosed by selective screening (MMA‐Cbl − : 10 % versus 39 %, p  = 0.002; GA1: 26 % versus 73 %, p  < 0.001). For other OADs, the clinical benefit of NBS was less clear. Reported age‐adjusted intake of natural protein and calories was significantly higher in LO patients than in EO patients reflecting different disease severities. Variable drug combinations, ranging from 12 in MMA‐Cbl − to two in isovaleric aciduria, were used for maintenance treatment. The effects of specific metabolic treatment strategies on the health outcomes remain unclear because of the strong influences of age at onset (EO versus LO), diagnostic mode (NBS versus selective screening), and the various treatment combinations used. Conclusions: NBS is an effective intervention to reduce time until diagnosis especially for LO patients and to prevent irreversible cerebral damage in GA1 and MMA‐Cbl − . Huge diversity of therapeutic interventions hampers our understanding of optimal treatment.